Ideal Characteristics of a Laser-Protected Endotracheal Tube: ABEA and AHNS Member Survey and Biomechanical Testing. (April 2018) - Friedman, Aaron D.; Gerber, Mark E.; Bhayani, Mihir K.; Kuchta, Kristine; Kumar, Kanav; Ma, Aobo; Ren, Yupeng; Zhang, Li-Qun
Objectives: To determine the characteristics of laser-protected endotracheal tubes (LPETs) valued by otolaryngologists performing transoral laser surgery in the head and neck and to measure LPET stiffness. Methods: An online questionnaire was completed by American Broncho-Esophagological Association (ABEA) and American Head and Neck Society (AHNS) members. LPET distal end compliance was measured in a biomechanics laboratory. Results: A total of 228 out of 2109 combined ABEA and AHNS members completed the survey. The following LPET characteristics, which were properties of the Medtronic Laser-Shield II tube (MLST), were highly valued: softness and flexibility, surface smoothness, and a tight-to-shaft balloon (all P < .01). Prior to industry-driven discontinuation of the MLST, 52% of surgeons (78% of fellowship-trained laryngologists [FTLs]) reported using it; afterward, 58% reported using the stainless steel, Mallinckrodt Laser-Flex tube (MLFT). Forty-six percent of all respondents (69% of FTLs) did not consider cost being a factor in LPET choice. Biomechanical testing revealed the distal end of the MLST to be 3.45 times more compliant than the MLFT ( P < .01). Conclusion: Members of the ABEA and AHNS, particularly FTLs, highly value distinguishing properties of the now discontinued MLST. Manufacturers should consider this in the design of new LPETs.